ANCAMAN OLIGARKI PARTAI DALAM PEMILU - Alrasyid, M. Harun (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
Political parties is an im because a balance of executive power through his representative in parliament representatives portant part of the political life of society, in the context of building democracy, the role of political parties in Indonesia occupies a strategic position. This paper attempts to review the party's role in the administration of elections in Indonesia.